Quantum Mechanical Approached to Time Travel - Alamgir Khan; Jamal Shah; Khurshid Ahmad (MultiTech Publisher, 2024)
Superposition allows quantum systems to persist simultaneously between multiple states until a unified time travel equation uses this concept for exploration of time travel potentials. The conception suggests that a quantum system occupies multiple timelines simultaneously in the same way that superposition exists in quantum mechanics which makes each time travel scenario an individual branch of the wave function. This technique allows expert analysts to manage paradoxes and develop complex perceptions about quantum time-based events. General relativity produces self-consistent patterns of closed timelike curves through the equation that depicts forward-time and backward-time system evolution. Quantum systems depend on the self-consistency condition to hold identical states throughout evolution periods for avoiding paradoxical problems including time travel contradictions. Quantum superposition operations enable systems through the equation to stay present simultaneously in multiple times for enhancing time travel rule development. The framework both fixes fundamental untrue logical flaws and enables operator’s better comprehension regarding time travel patterns among quantum frameworks. The time travel equation shows potential for quantum computing development by letting standard computer models solve unsolvable problems through simultaneous timeline evaluation and time loop control. The work presents an essential advancement in quantum mechanics research due to its explanation of time's relationship with quantum mechanical phenomena. Research and experimental ventures become possible because the unified time travel equation creates both a paradox-free modeling framework for time loops